Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd008834.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet agents for chronic kidney disease

Abstract: To evaluate the benefits and harms of antiplatelet therapy in patients with any form of kidney disease, including patients with CKD not receiving renal replacement therapy (RRT), patients receiving any form of dialysis, and kidney transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 117 publications
1
52
0
4
Order By: Relevance
“…28 A CV event may afford an opportunity for the clinician to intervene on the trajectory of these patients by aggressively mitigating subsequent morbidity and mortality associated with these events. Pooled data from clinical trials suggest evidence-based therapies, such as statins, 29 antiplatelet drugs, 30 β-receptor antagonists, 31 and angiotensin-converting enzyme inhibitors 32 have similar risk reduction profiles in patients with CKD not receiving dialysis as the general population and should be instituted when appropriate in CKD patients. Yet, previous studies have shown that a care gap exists for CKD patients after a CV event.…”
Section: Discussionmentioning
confidence: 99%
“…28 A CV event may afford an opportunity for the clinician to intervene on the trajectory of these patients by aggressively mitigating subsequent morbidity and mortality associated with these events. Pooled data from clinical trials suggest evidence-based therapies, such as statins, 29 antiplatelet drugs, 30 β-receptor antagonists, 31 and angiotensin-converting enzyme inhibitors 32 have similar risk reduction profiles in patients with CKD not receiving dialysis as the general population and should be instituted when appropriate in CKD patients. Yet, previous studies have shown that a care gap exists for CKD patients after a CV event.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review of the literature is out of the scope of this article, but suffice to say that there is an increasing body of research regarding the use of antiplatelets and oral anticoagulants in the CKD population 39 . A recent metaanalysis suggested that antiplatelet agents do reduce myocardial infarction in such patients but with significant increases in major bleeding, which may outweigh any potential benefits 40 . Data published on major bleeding events in dialysis patients gives a frequency of events of 2.5% per person-year, increasing to 4.4% with the use of aspirin alone and…”
Section: The Use Of Antiplatelet Agents In Uraemiamentioning
confidence: 99%
“…Drugs that are used in primary and secondary prevention strategies to lower stroke risk associated with these risk factors in the general population (including aspirin, warfarin, and statins) may be ineffective or even increase the risk of stroke in people with ESRD (7)(8)(9). In addition, novel risk factors specific to having ESRD (accelerated calcific atherosclerosis, platelet dysfunction, anemia, and frequent anticoagulation for those on hemodialysis) might increase stroke risk but may affect the risks of ischemic and hemorrhagic strokes differently (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%